Mumbai Local: Life Line or Life Stealing - Tyagi, Shashank; Sukhadeve, Rajesh B; Parchake, Manoj B; Pathak , Harish M (Journal of Indian Academy of Forensic Medicine, 2015)
Mumbai is financial and commercial capital of India. Mumbai wouldn’t have achieved this without the lifeline of the city–its local trains. Aim of our study was to find out most demographic profile manner and causes of death in railway deaths. Total number of 51 railway death cases was noted during study period. Most of the deaths belonging to younger age group 21 to 30 yrs (28%). Males (96.07%) preponderance was observed in our study. Maximum numbers of railway accidents were seen during the evening hours between 1600 to 2000 hrs. The majority of the victims were brought dead 27 (52%). Greatest number of deaths were accidental (98%) in nature. There were less suicidal cases (02%) and no case of homicidal death noted. Most common reason behind railway deaths was hit by train while crossing railway track 48% and 30% had fallen from running train due to overcrowding. Intracranial hemorrhage due to Head injury (47.05 %) was most common cause of death. Railway accidents can be preventable by taking appropriate measures such as attentive surveillance, ambulance availability at stations, safety engineering and awareness among passengers.